Effect of temperature on biology of red spider mite (Oligonychus coffeae) on three different TV clones - DAS, PURNIMA; SAIKIA, SIMANTA; KALITA, SURAJIT; HAZARIKA, LAKSHMI KANTA; DUTTA, SATYENDRA KUMAR (The Indian Journal of Agricultural Sciences, 2012)
An experiment to study the effect of temperature and diet on growth and development of the red spider mite (RSM), Oligonychus coffeae Nietner (Acarina : Tetranychidae) revealed prolongation of life cycle period up to 18.79 days at 20°C, which, however, was reduced to 8.06 days at 35°C. The longevity of adult male and female were 12.7 and 28.3 days, respectively at 20°C. Amongst the TV (Tocklai Vegetative) clones of tea, TV1 was found to be the most preferred diet, followed by TV10 and TV6. Fecundity was 120.7±21.74, 114.7±14.88 and 102.0±24.75 on TV1, TV6and TV10 respectively. The thermal constant needed for egg to adult formation ranged from 149.60 to 185.38 day°C on TV1 clone.